Challenges and Strategies of Hospitality EFL Lecturers in Implementing Industry-Based Learning within ESP Courses - Faradillah Saputri; Ratna Ratna (Institut Agama Islam Negeri (IAIN) Curup, 2026)
The rapid transformation of the hospitality industry in response to globalization and sustainability demands has placed new expectations on English for Specific Purposes (ESP) education. Within this evolving context, English as a Foreign Language (EFL) lecturers are required to bridge academic learning with professional practice through Industry-Based Learning (IBL). This study explored the challenges and strategies of hospitality EFL lecturers in implementing IBL within ESP courses in two Indonesian tourism polytechnics. Employing a qualitative descriptive approach, data were gathered through semi-structured interviews, classroom observations, and document analysis involving six EFL lecturers with direct experience in hospitality-based teaching. Thematic analysis revealed four interrelated themes: limited student readiness and linguistic confidence, inconsistent industry collaboration on sustainable practices, time constraints restricting learning depth, and pedagogical adaptation through scaffolding and reflection. These findings indicate that lecturers’ experiences are shaped by a continuous negotiation between institutional structures, industry realities, and the socio-emotional dimensions of teaching. The study highlights that successful IBL implementation depends not only on curriculum design but also on lecturers’ reflective and adaptive agency in managing authentic learning environments. Theoretically, the research contributes to the understanding of experiential and constructivist learning in vocational English contexts, while practically, it provides insights for strengthening collaboration among lecturers, institutions, and industry partners toward sustainable and contextually grounded hospitality education.